A metamorphosis of three-dimensional wave structure in transitional and turbulent boundary layers. (5th March 2021) - Jiang, X.Y.; Gu, D.W.; Lee, C.B.; Smith, C.R.; Linden, P.F.
Abstract: Abstract : Laminar–turbulent transition in boundary layers is characterized by the generation and metamorphosis of flow structures. However, the process of the evolution from a three-dimensional (3-D) wave to a $\varLambda$ -vortex is not fully understood. In order to develop a deeper understanding of the spatiotemporal wave-warping process, we present numerical studies of both K-regime transition and bypass transition. A qualitative comparison of flow visualizations between a K-regime zero pressure gradient (ZPG) case and an adverse pressure gradient (APG) case is done, based on the method of Lagrangian tracking of marked particles. In bypass transition, the development of a 3-D wave packet before the breakdown into a turbulent spot was visualized for both the linear and nonlinear stages. The underlying vortex dynamics was investigated using a proposed method of Lagrangian-averaged enstrophy. The study illustrates that a $\varLambda$ -vortex develops from a 3-D warped wave front (WWF), which undergoes multiple folding processes. It is observed that the APG case undergoes a more rapid evolution, precipitating a stronger viscous–inviscid interaction within the boundary layer. It is hypothesized that the amplification and lift-up of a 3-D wave causes the development of high-shear layers and a WWF. In order to seek a relationship between transitional and turbulent boundary layers, Lagrangian methods were also applied to an experimental data set from a turbulent boundary layer at low Reynolds number. Similarity of flow behaviours are observed, which further supports the hypothesis that the amplification of a 3-D wave precipitates low-speed streaks and rotational structures in wall-bounded flows.